MarControl for inland fishfarming in Iceland - Kristján Guðmundur Birgisson 1989- (2020)
Þetta var unnið í samstarfi með Maris ehf. This project is in collaboration with the company Maris ehf as they have set up and installed various control systems for land based fish-farms in Iceland. All the control systems are built around a PLC which has a logic program that will receive inputs from field devices and outputs to control others or said devices. Maris system controls pumps, food, oxygen, lights and water quality to name a few. Maris specializes in customizing their system to the need of the each costumer. Their next step is to have SCADA system on top of their control system to let the customer have better overview of their operations, and will help their customers to save expenses with the additional review on all their various monitored devices. The SCADA platform used by Maris ehf is from Schneider Electric called IGSS that is sold by their Icelandic sales representative,Fálkinn ehf. The SCADA system is developed by Maris ehf and has been named "MarControl". The platform has drivers that are able to communicate with PLC from the most known vendors and has also TCP/IP drivers that can connect to all TCP/IP PLC devices, and it is the most common communication in industry. That is a solution that if the costumer is geographically dispersed, that is if connection is lost between substation and the master station so the substation is automatically put into server mode and will store all values until connection resumes and will send all data to the master station. MarControl has been in development with Fálkinn and Schneider Electric, and is ready for installment when fish farms have given a green light on this upgrade. Verkefni þetta er unnið í samvinnu við Maris ehf sem hefur sett upp margvíslegan búnað í stýrikerfum fyrir fiskeldisfyrirtæki á þurru á Íslandi. Öll stýrikerfin eru byggð upp með PLC stýringum sem getur móttekið og sent upplýsingar til stýringar, meðal annars vegna dælingar, matargjafa, súrefnisdreifingu, ljósa og vatns. Maris sérhæfir sig í að hanna slíkar stýringar eftir óskum ...